2019
DOI: 10.1111/mcn.12708
|View full text |Cite
|
Sign up to set email alerts
|

Ethiopian mothers' experiences with micronutrient powders: Perspectives from continuing and noncontinuing users

Abstract: As part of a formative evaluation of a micronutrient powder (MNP) trial in Ethiopia that was organized according to a programme impact pathway model, we conducted in‐depth focused ethnographic interviews with caregivers of children between 6 and 23 months who had accepted to try “Desta,” a locally branded MNP. After stratification into two subgroups by child age, respondents were randomly selected from lists of caregivers who had received MNP from government health workers between 1 and 3 months prior to the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…The survey results showed that 22.9% of caregivers who stopped feeding Desta did so because they perceived that their children refused food mixed with it (Table 3). Our findings from the FES, which was conducted in a subsample of caregivers who participated in the trial (Pelto et al, 2019), provide insights for the interpretation of this result.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The survey results showed that 22.9% of caregivers who stopped feeding Desta did so because they perceived that their children refused food mixed with it (Table 3). Our findings from the FES, which was conducted in a subsample of caregivers who participated in the trial (Pelto et al, 2019), provide insights for the interpretation of this result.…”
Section: Discussionmentioning
confidence: 69%
“…These findings may be attributable to a natural evolution of taste preferences. Many children in the second and third years of life enter a "neophobic" phase during which some previously liked foods are no longer accepted, and the introduction of new foods becomes difficult (Nicklaus, 2009 Pelto et al, 2019). In the FES sample, six of the nine caregivers who reported problems with child refusal of food with Desta sought advice from HEW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…year of life as they experience periods of illness and poor appetite, and progress through developmental stages that affect feeding behaviours (G. Pelto et al, 2019). In Mozambique, we identified challenges in access to obtaining the supplement that had not been foreseen in the design and implementation of the delivery system (Tumilowicz, Vossenaar, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we draw on our experiences in two pilot projects that were undertaken to inform planning for scaling up the delivery of MNP in public health programmes in Ethiopia and Mozambique. Results of the evaluations are described in other papers in this supplement (G. H. Pelto et al, 2019;.…”
Section: Introductionmentioning
confidence: 99%